STRUCTURAL RELATIONSHIPS BETWEEN THE NEOGENE AND QUATERNARY ASSEMBLAGES; ACTIVE FAULTS, AND SEISMICITY IN SOUTHERN SAKHALIN - Rozhdestvenskiy V.S.; Saprygin S.M. (My University, 2001)
Seismic activity in southern Sakhalin is related to zones of submeridionally striking faults (upthrow and normal faults) separating ridges and intermountain depressions, and transorogenic faults of the NW (sinistral strike-slip faults) and NE (dextral strike-slip faults) strike. The observed system of active faults corresponds to a stereotype of fractures resulting from sublatitudinal and diagonal (azimuth 305°) horizontal compression. The seismic activity along the western side of the Susuya intermountain depression in the mid-Quaternary shifted from the Tym-Poronai fault, crosscutting the Pliocene-Early Quaternary and mid-Quaternary leveling planes, to the Aprelovka fault, displacing the Late Pleistocene and Holocene assemblages. The Lower Pleistocene deposits of the Susuya depression occur conformably together with Pliocene assemblages of a molasse formation (Maruyam suite). Since paleoseismodeformations indicating catastrophic Holocene earthquakes are known over the entire territory of the island, including regions currently aseismic, it is demanded that a study of active faults be performed in the whole territory of Sakhalin and adjoining water areas aimed at diagnosing earthquake frequency and a long-term prediction of seismic hazards.
Keywords: Pleistocene; Holocene; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен